A Compact High-Efficiency Broadband Rectifier With a Wide Dynamic Range of Input Power for Energy Harvesting - He, Zhongqi; Liu, Changjun (IEEE microwave and wireless components letters, 2020)
In this letter, a compact high-efficiency broadband microwave rectifier with an extended range of input power is proposed for energy harvesting. In the proposed structure, a novel broadband impedance-matching network is employed to reach high radio frequency (RF) to dc conversion efficiency. The reduction in mismatching loss over a wide bandwidth and input power range is achieved by impedance transformation from three segments of microstrip lines, which leads to a compact design to realize broadband impedance matching. A theoretical analysis and simulations of the proposed rectifier are presented. For validation, a broadband rectifier operating between 2.1 and 3.3 GHz is implemented and tested. The proposed rectifier shows a bandwidth of 44.4% for efficiency over 70% at an input power of 14 dBm. The measured efficiency remains above 50% from 2 to 3.3 GHz with an input power from 4 to 16 dBm. Moreover, the proposed rectifier has a compact size of 31 mm ×18 mm.